Potato production affected by fertilization methods, masses of seed tubers and water regimes - Viana, Jonathan Dos S. [UNESP]; Palaretti, Luiz Fabiano [UNESP]; de Faria, Rogério T. [UNESP]; Delgado, Yago V. [UNESP]; Dalri, Alexandre B. [UNESP]; Barbosa, José de A. [UNESP] (FapUNIFESP (SciELO), 2020)
Increasing potato yield while saving natural resources is a challenge for all those involved in the potato production chain. A field experiment was carried out in order to evaluate the effect of different levels of fertilization, mass of seed tubers and the water regime on the production of potato cv. Orchestra. We tested fertilization methods (F1= conventional fertilization; F2= fertigation according to the rate of absorption by the crop; F3= fertigation split into 3 applications), seed tuber mass (ST1= <50 g; ST2= >50 g), and water regimes [WR1= 50%; WR2= 100% replacement of crop evapotranspiration (ETc)]. The study was conducted using a split-plot randomized block design, with fertilizers in the plot and seed tuber mass in the subplot, with six replications. The highest tuber yields (48.18 t ha-1) and greatest potatoes (43.67 t ha-1) were obtained in the treatment F2 and for seed tuber masses >50 g (48.61 and 42.78 t ha-1) under 100% ETc water regime. However, for plants subjected to 50% ETc, the factors fertilization and seed tuber mass caused no difference in tuber yield (P>0.05). The highest water use efficiency (39.82 kg m-3 of water) was found under WR of 50% ETc for seed tuber masses >50 g. The highest cover ratio was obtained with tubers under 100% ETc being 89 days the cycle duration. The fertilization method and seed tuber mass that positively influenced the studied variables were fertigation according to the culture absorption rate and seed tuber masses >50 g for both water conditions (100% and 50% ETc).
Produção de batata sob diferentes métodos de fertilização, massas de tubérculos sementes e regimes hídricos
Keywords: Drip irrigation; Nutrition; Propagation; Solanum tuberosum